2022
DOI: 10.1007/s10654-022-00873-6
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior and cancer–an umbrella review and meta-analysis

Abstract: Several systematic reviews and meta-analyses have summarized the association between sedentary behavior (SB) and cancer. However, the level of evidence and the potential for risk of bias remains unclear. This umbrella review summarized the current data on SB in relation to cancer incidence and mortality, with a particular emphasis on assessing the risk of bias. We searched PubMed, Web of Science and Cochrane Database for systematic reviews and meta-analyses on the association between SB and cancer incidence an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 88 publications
0
27
3
Order By: Relevance
“…Additionally, the sample size of this study was large enough to provide sufficient statistical validity for the detection of a convincing association. Notably, in addition to poor dietary habits, other risk factors such as obesity, smoking, alcohol consumption, sedentary behavior, and exposure to pesticides are also associated with an increased risk of CRC [ 71 , 72 , 73 , 74 , 75 ]. We excluded the effect of these risk factors mainly by adjusting them as confounding factors in the multivariable models.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sample size of this study was large enough to provide sufficient statistical validity for the detection of a convincing association. Notably, in addition to poor dietary habits, other risk factors such as obesity, smoking, alcohol consumption, sedentary behavior, and exposure to pesticides are also associated with an increased risk of CRC [ 71 , 72 , 73 , 74 , 75 ]. We excluded the effect of these risk factors mainly by adjusting them as confounding factors in the multivariable models.…”
Section: Discussionmentioning
confidence: 99%
“…found sedentary time measured by the ActiGraph GT3X was not associated with fatigue. Several reviews have suggested sedentary time is associated with increased cancer mortality 35,36 but consistent evidence implicating sedentary time in adverse QOL and other PROs has not emerged. Inconsistent results across these studies may be due to key methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have begun to focus on the significance of modifiable behavioral factors in cancer development and progression, particularly the potential associations among SB, PA, and cancer. Numerous epidemiological studies have found that appropriate PA reduces the risk and improves the prognosis of several cancers, while SB has the exact opposite effect ( 10 , 11 ). Nevertheless, SB and low PA levels are becoming increasingly common in modern lifestyles, both in the healthy population and among cancer survivors.…”
Section: Introductionmentioning
confidence: 99%